Morbidade hospitalar materno-infantil Yanomami, Brasil (2008-2012) - Caldart , Raquel Voges (2014)
The aim of this study was to identify the causes of morbidity in maternal and child Yanomami population, from Amazonia, Brazil, in the period 2008-2012. The causes of hospitalization were investigated in two public hospitals located in Boa Vista, Roraima, Brazil: Hospital da Criança Santo Antônio and Hospital Materno-Infantil Nossa Senhora de Nazareth, both hospitals are the only references to the population under health responsibility of the Distrito Sanitário Especial Indígena Yanomami. It was identified 1023 records regarding to children hospitalization and 332 records regarding obstetric hospitalization. The main causes of hospitalization among children, according to the International Classification of Diseases were: respiratory diseases (53,9%); infectious and parasitic diseases (19,5%); and nutritional diseases (12,1%), this profile of hospitalization causes is in accordance with poor health conditions. Children under one year old were responsible for the highest number of hospitalizations and the highest rates of hospital mortality. During the five years surveyed observed an increase in hospitalizations for respiratory diseases. Among obstetric admissions predominated hospitalizations for childbirth care (51,5%); followed by clinical complications during pregnancy (32,8%); abortion (11,4%) and clinical events after delivery (4,2%). Most deliveries were vaginal deliveries, however, the rate of cesarean section was higher than recommended by the World Health Organization. Women between 15-35 years old were responsible for the highest number of obstetric hospitalization, no record of maternal death was observed during the five years of survey. The analysis of hospitalizations in the different regions of Yanomami Territory demonstrated different profiles and complex situations in the regions with lower rates of hospitalization related to poor access to health services.